The Training Needs Of Mathematics Teachers In Light Of The Developed Collins Mathematics Curricula In Jordan (Journal of Namibian Studies : History Politics Culture, 2024)
e study aimed to investigate the training needs of mathematics teachers in light of the globally developed Collins mathematics curricula. The study adopted a descriptive research methodology, and its tools included a questionnaire developed by the researcher. A total of 266 mathematics teachers from the first educational directorate in Irbid, Jordan, participated in the study, selected through stratified random sampling. The study revealed that the degree of all training needs was high, with the order of training needs fields from highest to lowest being: specialization, educational, and pedagogical. The most crucial training needs (degrees as very high) for mathematics teachers were: training on using teaching strategies suitable for the developed mathematics curricula, training on using assessment strategies suitable for the developed mathematics curricula, and understanding the mathematical concepts included in the developed mathematics curricula. The study also showed no statistically significant differences based on the variables of academic qualification and gender among mathematics teachers. The study recommended the necessity of training teachers on the identified training needs.